Handbook of production management methods - Halevi, Gideon, 1928- (Butterworth-Heinemann, 2001)
This unique book provides a guide to the selection of appropriate production and manufacturing methods for postgraduate and professional manufacturing engineers. It starts by helping the reader to identify the required objectives of industrial management for their particular situation. Having identified the objectives an analytical assessment of the available production and management methods is made. The analytical system presents an objective method of production selection. For example, this practical book will help the reader to decide whether or not a local Just-in-Time process is needed or a full chain JIT method is needed. Alternatively the problem may be deciding between set-up time reduction or changeover time reduction. Should TQM be ceded to PCIs? This book covers nearly all methods of production and manufacturing and will prove the most comprehensive guide to choosing and using these methods. Only book of its kind availableWidest coverage of methods availableAnalytical approach to decision making.
Keywords: Production management.; Manufacturing processes.; elektronické knihy; electronic books